Cyber Risks for Business Professionals : a Management Guide. - Kendrick, Rupert (IT Governance Pub., 2010)
Cyber Risks for Business Professionals: A Management Guide is a general guide to the origins of cyber risks and to developing suitable strategies for their management. It provides a breakdown of the main risks involved and shows you how to manage them. Covering the relevant legislation on information security and data protection, the author combines his legal expertise with a solid, practical grasp of the latest developments in IT to offer a comprehensive overview of a highly complex subject.